Evidence that olfactory sensitivities to calcium and sodium are mediated by different mechanisms in the goldfish Carassius auratus - Hubbard, Peter (2014)
The current study investigated whether the olfactory sensitivity to Ca2+ and Na+ is mediated by the same mechanism in the goldfish, a freshwater teleost. The olfactory responses, as assessed by recording the electro-encephalogram (EEG) from the olfactory bulb, to changes in external [Ca2+] and to [Na+] were recorded in the absence and presence of increasing concentrations of the other ion. Low concentrations of Na+ (0–1.0 mM) had no significant effects on the olfactory response to changes in [Ca2+] in terms of EC50, Imax or Hill co-efficient (n = 8). A relatively high concentration of Na+ (10 mM) significantly reduced the Imax and increased the EC50. One hundred millimolars Na+reduced the olfactory response to Ca2+ to undetectable levels. Conversely, low concentrations of Ca2+ (0.1 and 1.0 mM) significantly attenuated the olfactory response to changes in environmental [Na+], reducing the amplitude of response and increasing the threshold of detection (n = 7). However, a high concentration of Ca2+ (10 mM) failed to attenuate the olfactory response to Na+ completely. Taken together, these results suggest that, at normal environmental concentrations of these ions, Ca2+ and Na+ are detected by distinct and separate cellular mechanisms. However, there seems to be a degree of overlap between the two mechanisms. The exact mechanisms involved, and their biological roles, remain to be established.